BUSINESS DEVELOPMENT STRATEGIES FOR SAGO PROCESSING IN MERAUKE REGENCY: A BUSINESS MODEL CANVAS AND SWOT ANALYSIS - Rico Kuntag, Jacobus; Fernando Richard, Yumiad; Awal, Muhammad (Penerbit Lafadz Jaya, 2025)
This study aims to identify and analyze business development strategies for sago processing in Merauke Regency to enhance competitiveness and sustainability. Utilizing the Business Model Canvas method and SWOT analysis, the study reveals key challenges in production management, including limited processing technology, financial management issues, and marketing management constraints. To address these challenges, investment in advanced technology, managerial training, and effective marketing strategies are required. This research provides practical guidelines for sago processing business actors and contributes academically to the fields of sustainable marketing and SME development.